Pembacaan Progresif Ayat Feminis: Telaah Penafsiran Sahiron Syamsuddin dan Asghar Ali Engineer atas QS. An-Nisā’ [4]: 34 - Muhammad Syafirin (Kuras Institute, 2024)
The classical mufasirs’ interpretation of QS. an-Nisā’ [4]: 34 often leads to gender bias. An understanding that tends to be literal-scripturalistic-normative implies a view that the superiority of men over women is considered an Islamic decree. This article aims to examine the extent to which the verse is understood based on the views of two figures, namely Sahiron Syamsuddin and Asghar Ali Engineer. Based on library research, and through a textual analysis approach to the interpretation of the two figures above, this research shows that QS. an-Nisā’ [4]: 34 is not simply seen as a normative verse as understood by classical mufasirs and some modern mufasirs, but also as a verse that describes the real conditions of the Arab family system at the time of the Prophet which is being morally organised by the Qur’an. So, in addition to being normative, the verse must also be understood as a historical-cultural verse. Thus, the authority of family leadership is no longer understood as a private space belonging to men alone, but is determined by the prevailing system culture. In a matriarchal family system, a wife can be a leader, as well as in a collective system, as long as the leadership provides justice and benefits for the family.